A metabolomics approach used to profile plasma from portal–arterial pigs revealed differences between breads incurred by dietary fibre and protein contents. (22nd August 2014) - Nielsen, Kirstine Lykke; Hedemann, Mette Skou; Lærke, Helle Nygaard; Jørgensen, Henry; Bach Knudsen, Knud Erik
Abstract: A liquid chromatography–MS (LC-MS) metabolomics analysis of plasma from portal–arterial catheterised pigs fed breads prepared with whole-grain rye or wheat flour with added concentrated arabinoxylan (AX) or β-glucan (BG) was conducted. Comparison of the effects of concentrated fibres with whole grains has received little attention. Six female catheterised pigs were given two white wheat breads with wheat AX or oat BG, two rye breads with ground rye (GR) or intact rye kernels (RK), and a control white wheat bread (WF) on separate occasions in a randomised cross-over design. The amount of available carbohydrate was similar for the five breads but varied in the content of protein. Plasma was collected continuously for 4 h after feeding. Glucose levels in the portal vein were reduced postprandially in response to the AX, GR and RK breads that had high contents of AX compared with WF bread ( P < 0·03). AX and RK breads further tended to decrease plasma levels of some lysophosphatidylcholine species ( P ≤ 0·10). The abundance of amino acids in plasma correlated with the protein contents in the breads and leucine uptake significantly affected insulin secretion in the mesenteric artery. In conclusion, the present study revealed that concentrated AX in wheat bread had similar positive effects as whole-grain rye bread on glucose and lipid metabolism.